Neurobiology of Attention 2005
DOI: 10.1016/b978-012375731-9/50078-1
|View full text |Cite
|
Sign up to set email alerts
|

External Noise Distinguishes Mechanisms of Attention

Abstract: Attention to objects or features of objects affects performance on perceptual tasks such as detection, recognition, or identification. The speed or accuracy of task performance can be significantly influenced by changes in the state of attention, especially in complex task environments. The state of attention may be manipulated by specific environmental cues, or by decisions about allocation of attention induced by task demands. The challenge is to understand and predict these attention-mediated changes in tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
148
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 14 publications
15
148
1
5
Order By: Relevance
“…By what mechanism does attention improve spatial resolution? An improved signal-to-noise ratio (SNR) at the attended location contributes [2], due to retinotopically-specific signal gain [310]. Additionally, attention could sharpen position tuning at the neural population level, so that adjacent objects activate more distinct regions of visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…By what mechanism does attention improve spatial resolution? An improved signal-to-noise ratio (SNR) at the attended location contributes [2], due to retinotopically-specific signal gain [310]. Additionally, attention could sharpen position tuning at the neural population level, so that adjacent objects activate more distinct regions of visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars show 95% confidence intervals. (Dosher & Lu, 2000;Lu & Dosher, 1998). Inefficient perceptual categories could impair the recognition of letters and letter sequences and thus hamper reading efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…(17)). Lu and Dosher (1998) have shown that these two processes are mathematically equivalent in the PTM framework, and are empirically indistinguishable. Signal enhancement and additive noise reduction will lower thresholds primarily in conditions where external noise is low.…”
Section: Mechanisms Of Learningmentioning
confidence: 99%